Peran Kepemimpinan Kepala Sekolah sebagai Motivator dalam Meningkatkan Kinerja Guru - Saefudin (JMPT: Jurnal Manajemen Pendidikan Tihamah, 2023)
This study aims to determine the principal's leadership as a motivator in improving teacher performance at SD Negeri 2 Tegalsari. This research is a type of qualitative research with data collection techniques through interview techniques, observation and documentation studies while the validity of the data through tests of credibility, transferability depenbilitas and confirmability. The results of this study found that the type of leadership can increase the discipline of students at SD Negeri 2 Tegalsari by creating good communication, mutual support and being able to fulfill their responsibilities in leading the school principal and good cooperation is also needed with their subordinates to control and supervise students. students, students' awareness of the importance of discipline and the support of parents and the surrounding community. The conclusion in this study is to develop a plan to improve discipline in SD Negeri 2 Tegalsari which is carried out by teachers, education staff, guardians of students so that they feel responsible for the implementation of student discipline.